Strategi Digital Marketing yang Dilakukan The Portrait Place melalui Media Sosial Instagram - Annisa Oktaviani Bekti; Dede Lilis Chaerowati (UNISBA Press, 2024)
Abstract. Research on digital marketing has been carried out at The Portrait Place which is engaged in business in the field of photography services. The Portrait Place is a business in the service sector, namely photography. The purpose of this research is to find out digital marketing strategies carried out through Instagram @theportraitplace.id. The subject of this research is CMO from The Portrait Place and Marketing from The Portrait Place and who manages Instagram from The Portrait Place. The theory used in this research is Marketing Strategy, and POAC Theory. The method used in this study is a qualitative research method with a case study approach and a constructivism paradigm. Data collection techniques used are observation, interviews and documentation. Data analysis was carried out in a qualitative descriptive manner. The results of the study are: (1) The Portrait Place uses Instagram because Instagram has superior user demographics and feature advantages, as well as a form of adaptation to information technology developments; (2) Planning is carried out by looking at public trends and strengthening corporate character which is implemented through various patterns and characteristics such as color; (3) The organizing process is carried out with the stages of distributing human resources and dividing tasks in the Standard Operational Procedure Digital Marketing The Potrait Place; (4) The implementation process is carried out by looking at the use of viral moments and trends as well as market segmentation and the implementation of digital marketing concepts at The Portrait Place; (5) The control process is carried out by evaluating digital marketing content on Instagram The Portrait Place and conducting research and comparisons with other similar companies. The problems that arise in digital marketing at The Potrait Place, such as the inconsistency of Insight Digital Marketing Instagram, are resolved by adjusting the digital marketing public and updating The Potrait Place Digital Marketing in terms of concepts. From this research it can be concluded that 1) Instagram plays an important role in supporting today's business; 2) Digital Marketing Standard Operational Procedure (SOP) is made in the planning process; 3) SOP is used in organizing for human resources and their duties; (4) at the implementation stage new marketing content was born on Instagram The Potrait Place; and 5) the results of controlling and evaluating The Potrait Place updating digital marketing content on Instagram. Abstrak. Telah dilakukan penelitian mengenai digital marketing pada The Portrait Place yang bergerak dalam usaha di bidang jasa fotografi. The Portrait Place merupakan sebuah usaha di bidang jasa yaitu fotografi. Adapun tujuan dari penelitian ini yaitu untuk mengetahui strategi digital marketing yang dilakukan melalui Instagram @theportraitplace.id. Subjek penelitian ini CMO dari The Portrait Place dan Marketing dari The Portrait Place dan yang mengelola Instagram dari The Portrait Place. Teori yang dipakai pada penelitian ini yaitu Strategi Marketing, dan Teori POAC. Metode yang digunakan dalam penelitian ini yaitu metode penelitian kualitatif dengan pendekatan studi kasus serta paradigma konstruktivisme. Teknik pengumpulan data yang digunakan adalah observasi, wawancara dan dokumentasi. Analisis data dilakukan secara deskriptif kualitatif. Hasil dari penelitian, yaitu: (1) The Potrait Place menggunakan Instagram dikarenakan Instagram memiliki keunggulan demografi pengguna dan keunggulan fitur, serta sebagai bentuk adaptasi perkembangan teknologi informasi; (2) Perencanaan dilakukan dengan melihat tren publik dan penguatan karakter perusahaan yang diimplementasikan melalui berbagai corak dan ciri khas seperti warna; (3)Proses pengorganisasian dilakukan dengan tahapan pembagian sumber daya manusia serta pembagian tugas pada Standard Operational Procedure Digital Marketing The Potrait Place; (4) Proses pelaksanaan dilakukan dengan melihat pemanfaatan viralitas momen dan tren serta segmentasi pasar dan implementasi konsep digital marketing pada The Potrait Place; (5) Proses pengendalian dilakukan dengan melakukan evaluasi konten digital marketing pada Instagram The Potrait Place serta melakukan riset dan perbandingan dengan perusahaan lain yang sejenis. Adapun permasalahan yang muncul dalam digital marketing The Potrait Place seperti inkonsistensi Insight Digital Marketing Instagram yang diatasi dengan cara melakukan penyesuaian publik digital marketing serta melakukan Update Digital Marketing The Potrait Place dari segi konsep. Dari penelitian ini dapat disimpulkan bahwa 1) Instagram berperan penting dalam menunjang bisnis masa kini; 2) Standard Operational Procedure (SOP) Digital Marketing dibuat pada proses perencanaan; 3) SOP digunakan pada pengorganisasian untuk sumber daya manusia dan tugasnya; (4) pada tahap pelaksanaan terlahir konten-konten pemasaran baru pada Instagram The Potrait Place; dan 5) hasil dari pengendalian serta evaluasi The Potrait Place melakukan pembaharuan konten-konten digital marketing pada Instagram.